2015
DOI: 10.2471/blt.14.145771
|View full text |Cite
|
Sign up to set email alerts
|

Injury-related mortality in South Africa: a retrospective descriptive study of postmortem investigations

Abstract: ObjectiveTo investigate injury-related mortality in South Africa using a nationally representative sample and compare the results with previous estimates.MethodsWe conducted a retrospective descriptive study of medico-legal postmortem investigation data from mortuaries using a multistage random sample, stratified by urban and non-urban areas and mortuary size. We calculated age-specific and age-standardized mortality rates for external causes of death.FindingsPostmortem reports revealed 52 493 injury-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 11 publications
(18 reference statements)
9
106
0
1
Order By: Relevance
“…From personal experience (LJM serves as a member of the National Forensic Pathology Service Committee) and involvement in national mortality-based studies of two of the authors (SM and LJM), it is suggested that the Western Cape referral pattern is different from the national referral pattern in that most SUDIs are not referred to the FPS, but declared as natural deaths by medical practitioners in the community, and are therefore never brought to the attention of the health surveillance system. [13,14] A concern is the potential for child homicides, in particular deaths from neglect, to remain undetected. This may also place other children in the family at risk.…”
Section: Child Deaths In South Africa: Lessons From the Child Death Rmentioning
confidence: 99%
“…From personal experience (LJM serves as a member of the National Forensic Pathology Service Committee) and involvement in national mortality-based studies of two of the authors (SM and LJM), it is suggested that the Western Cape referral pattern is different from the national referral pattern in that most SUDIs are not referred to the FPS, but declared as natural deaths by medical practitioners in the community, and are therefore never brought to the attention of the health surveillance system. [13,14] A concern is the potential for child homicides, in particular deaths from neglect, to remain undetected. This may also place other children in the family at risk.…”
Section: Child Deaths In South Africa: Lessons From the Child Death Rmentioning
confidence: 99%
“…Fires kill thousands of people every year, with many more disabled or seriously injured, resulting in untold and often lifelong misery and entrenched poverty. [13] These deaths are mainly categorised as owing to flame burns, although in informal settlements liquid and food burns are also a significant cause of burn injury and hospitalisation. In SA, children are a vulnerable population, because of their more limited risk appraisal capacities and physiology.…”
Section: Shack Fires and Child Burn Injuriesmentioning
confidence: 99%
“…[12] The misclassification of injury deaths is another major limitation. [2,13] The Inquest Act of 1959 [14] precludes forensic pathologists from reporting the manner of death, i.e. whether it is due to homicide, suicide, transport or other unintentional injuries, on the basis that it may prejudice the findings of the inquest.…”
Section: Editorialmentioning
confidence: 99%
“…[1] Police statistics on homicide, and transport deaths from the Road Traffic Management Corporation, are considered to be under-reported [2] and are not a reliable source for monitoring SDGs.…”
Section: Editorialmentioning
confidence: 99%